Approving Restoration Mechanism in 7075 Aluminum Alloy through Constitutive Flow Behavior Modeling. Issue 6 (29th December 2015) - Moghaddam, Mohammad; Zarei‐Hanzaki, Abbas; Farabi, Ehsan; Taheri‐Mandarjani, Mahsa
Abstract : The present study deals with the flow stress characterization of 7075 aluminum alloy using process maps and constitutive flow behavior modeling. The latter was performed employing the work hardening‐DRV and DRX based models. The hot compression tests data in a wide range of temperature and strain rate were used to develop the activation energy map, strain rate sensitivity map, and the processing maps. Furthermore, in comparison with previously hired models, the DRX based model showed a good compatibility with the experimental results and therefore it was approved as a novel technique to justify the main restoration mechanism in 7075 aluminum alloy. Abstract : The hot flow behavior characteristic of 7075 aluminum alloy has been studied through processing maps . For a deeper understanding of main restoration mechanism, constitutive equations has been elaborated. It was proposed that DRX based model, in comparison with other employed models, not only predicts the material's flow behavior but also can be used to predict the main restoration mechanism.